2020
DOI: 10.1249/jsr.0000000000000732
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Ketosis with Ketogenic Diets or Exogenous Ketones: Features, Convergence, and Divergence

Abstract: Athletes, clinicians, and practitioners are increasingly interested in the proposed performance and therapeutic benefits of nutritional ketosis (NK). NK is best operationally defined as a nutritionally induced metabolic state resulting in blood β-hydroxybutyrate concentrations of ≥0.5 mM. Most tissues readily metabolize ketone bodies (KBs), and KBs in turn regulate metabolism and signaling in both a systemic and tissue-specific manner. During fasting, starvation, or ketogenic diets, endogenous synthesis of KBs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
72
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 51 publications
0
72
0
1
Order By: Relevance
“…Interest into the health, disease, and performance impact of exogenous ketone bodies has rapidly expanded due to the multifaceted physiologic and signaling properties ascribed to these metabolites (1,7,36). Various natural and synthetically derived forms currently exist with emergent evidence indicating convergent and divergent impacts across various physiologic and metabolic parameters (1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interest into the health, disease, and performance impact of exogenous ketone bodies has rapidly expanded due to the multifaceted physiologic and signaling properties ascribed to these metabolites (1,7,36). Various natural and synthetically derived forms currently exist with emergent evidence indicating convergent and divergent impacts across various physiologic and metabolic parameters (1).…”
Section: Discussionmentioning
confidence: 99%
“…Ketones bodies are metabolic end products of lipid metabolism traditionally produced during fasting/starvation, severe caloric restriction, or low carbohydrate diets (1). Endogenous ketone production is predominantly regulated via insulin and glucagon levels on adipose and hepatic tissue, respectively (2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 1,3 butanediol backbone enters hepatic circulation and is subsequently catabolized via alcohol and aldehyde dehydrogenases into βHB. Consequently, all exogenous ketone bodies result in subsequent elevations in circulating ketone body elevations, but with diverse kinetics, tolerance, and application impact [1,3,6,7]. Sport and/or athletic practitioners have been interested in exogenous ketone bodies dating back for almost a half-century when MCT's their potential metabolic and performance impact in isolation or combination with other exogenous nutrients under the hypothesis that providing additional and diverse metabolite availability may augment sport related performance outcomes [5].…”
Section: Introductionmentioning
confidence: 99%
“…Of interest were the ndings that βHB-salts+MCTs augmented and prolonged elevations in circulating βHB compared to βHB-salts alone, illustrating unique metabolic impact [3]. Additionally, this unique mixture lowers the acute mineral and MCT load, potentially mitigating gastrointestinal impact [1]. Consequently, our group explored the metabolic and performance impact of βHB-salts and MCTs on 5-km running in well trained runners and found that this was well tolerated, altered systemic metabolism, and augmented and attenuated 8/10 and 2/10 5k runner performance, respectively [25].…”
Section: Introductionmentioning
confidence: 99%